2013
DOI: 10.1123/japa.21.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Versus Functional Strength Training: Effects on Muscle Strength and Power in the Elderly

Abstract: The aim was to determine whether strength training with machines vs. functional strength training at 80% of one-repetition maximum improves muscle strength and power among the elderly. Sixty-three subjects (69.9 ± 4.1 yr) were randomized to a high-power strength group (HPSG), a functional strength group (FSG), or a nonrandomized control group (CG). Data were collected using a force platform and linear encoder. The training dose was 2 times/wk, 3 sets × 8 reps, for 11 wk. There were no differences in effect bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 38 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…Moreover, both groups experienced similar significant increases in the maximal dynamic strength and muscle power tests, corroborating the results obtained by Lohne-Seiler et al, 25 where after 11 weeks of intervention found no significant differences between groups that practiced functional strength exercises versus traditional strength exercises with respect to the traditional maximum dynamic force test and muscle power in the Leg-press test. However, it is worth noting that the maximum dynamic strength and muscle power tests applied in the present investigation were executed in machines used by the TT group in daily basis, and their significant performance may be related to the training specificities to the tests.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, both groups experienced similar significant increases in the maximal dynamic strength and muscle power tests, corroborating the results obtained by Lohne-Seiler et al, 25 where after 11 weeks of intervention found no significant differences between groups that practiced functional strength exercises versus traditional strength exercises with respect to the traditional maximum dynamic force test and muscle power in the Leg-press test. However, it is worth noting that the maximum dynamic strength and muscle power tests applied in the present investigation were executed in machines used by the TT group in daily basis, and their significant performance may be related to the training specificities to the tests.…”
Section: Discussionsupporting
confidence: 80%
“…Two important factors promoting self-care in older people 75+ years of age are self-care agency and frequency of physical activity 4. These results accompany studies on the importance of physical activity in older age,1316 as well as the importance of keeping up with activities for self-care 8,1719…”
Section: Introductionmentioning
confidence: 69%
“…However, functional strength training has taken a different course today, functional strength training is a range of total-body activities that build strength, Power, balance and coordination for general fitness, and improve lifters ability to perform lifting. Although functional strength training commonly is perceived as a form W Gharib, 2018 Turk J Kin 2018; 4(2): 47-52 of core training, core training could be considered a subset of functional strength training (Lohne-Seiler et al, 2013). Functional strength training is the basic training is the practice of unrestricted movement against resistance, focusing on stabilizer muscles of your back, abdomen and sides extends the same training to the entire body (Ng et al, 1998).…”
Section: Introductionmentioning
confidence: 99%